(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2018)
The article refers to Georgian Literature of the 20th and it analyzes the difficulties in the idelogical implication of the world literary processes. Author discusses the novels of different Georgian writers and tries to outline the role of writing in the world culture. Author tells about the influence of Soviet Union in Georgian literature and how it affected the mission of Georgian writers in their novels. Author tries to analyze the confronting the most complicated political regimes with writing and science. Author discussess the role of Cummunism and its outputs and inputs in writing and literature. The objective of the article is to show the special mission and aims of Georgian writers.